2016
DOI: 10.1002/jee.20118
|View full text |Cite
|
Sign up to set email alerts
|

Identity, Critical Agency, and Engineering: An Affective Model for Predicting Engineering as a Career Choice

Abstract: Background Prior to college, many students have no experience with engineering, but

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
520
5
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 435 publications
(549 citation statements)
references
References 108 publications
(114 reference statements)
21
520
5
3
Order By: Relevance
“…Understanding why students choose engineering in college can help identify avenues through which more students can see themselves as engineers and choose engineering as a career before routes into engineering are more difficult to pursue. Prior work has shown that developing math-and science-related identities and developing motivation to accomplish far-off goals are important attributes for students choosing and wishing to persist in engineering fields (Godwin, Potvin, Hazari, & Lock, 2016). This work is an extension of a prior study examining how students' out-of-school experiences predicted engineering identity at the beginning of college, future engineering certainty, and gender differences to further explore how interests in STEM-related activities before college can impact disciplinary engineering choice (Godwin, Sonnert, & Sadler, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding why students choose engineering in college can help identify avenues through which more students can see themselves as engineers and choose engineering as a career before routes into engineering are more difficult to pursue. Prior work has shown that developing math-and science-related identities and developing motivation to accomplish far-off goals are important attributes for students choosing and wishing to persist in engineering fields (Godwin, Potvin, Hazari, & Lock, 2016). This work is an extension of a prior study examining how students' out-of-school experiences predicted engineering identity at the beginning of college, future engineering certainty, and gender differences to further explore how interests in STEM-related activities before college can impact disciplinary engineering choice (Godwin, Sonnert, & Sadler, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The stronger effect of holding an engineering possible self on choosing engineering has significant implications for how students select engineering in college and their motivation to remain in engineering over time. While subject-related identities in math and science have proven important for both men and women in their choice of engineering 25 , a future identity in engineering, or possible self may be a stronger link to engineering decisions. Being female decreases the likelihood of choosing engineering in college by approximately one half times.…”
Section: Resultsmentioning
confidence: 99%
“…The National Research Council stated that out-of-school science experiences have a positive impact on education because they promote interest in science within the real world 22 . Fostering interest in a science-related area has been shown to motivate STEM career choice and persistence 21,[23][24][25] . Research on informal science has begun to examine how these experiences influence students' career choice.…”
Section: Introductionmentioning
confidence: 99%
“…To characterize normative and non-normative attitudinal profiles of engineering majors, a survey instrument was developed to capture several student factors: students' STEM-related identities [17][18][19][20][21][22] , personal motivations (including items assessing future time perspective 40,41 and goal orientation 42 ), career outcome expectations and major intentions 43 , agency beliefs 5 , grit 44 , and personality profile 45 , along with demographic information. Many of the survey items measuring demographic information were specially developed for this project.…”
Section: Quantitative Methodsmentioning
confidence: 99%
“…Otherwise, if the opportunity is lost, transitions into engineering in college are difficult, and the engineering community will largely remain as it is today. While attitudes toward engineering and science careers may begin to form in middle school, high school science and math experiences have a large effect on students' later choice of engineering as a career [3][4][5] .…”
Section: Introductionmentioning
confidence: 99%